Trunthung Music: Presenting Performances in The Context of Ecotourism - Fajry Sub'haan Syah Sinaga; Emah Winangsit; Triyanto Triyanto; Udi Utomo; Syahrul Syah Sinaga (Universitas Negeri Semarang, 2021)
This study aims to describe the interrelationship of Trunthung Music performances which are presented as tourism packages in Magelang Regency. The various events held presented Trunthung Music as a manifestation of local potential that represents environmental conditions in Magelang, starting from the Borobudur Temple, to the geographical conditions surrounded by five mountains, namely Merapi, Merbabu, Andong, Sumbing, and Menoreh Mountains. This study uses the concept of ecomusicology that combines elements of music, culture, and the environment. This research is a qualitative research with data collection methods obtained using the method of observation, interviews, and documentation. The results of this study indicate that Trunthung Music performances are music that grows and develops on the role of Sutanto Mendut and farmer artists from Merbabu. Handoko and Riyadi are artists who continue to develop Trunthung Music performances, until now Trunthung Music is a performance that represents the environment and culture in tourism packages around Magelang Regency.